Real rigidities and the cross-sectional distribution of price stickiness: Evidence from micro and macro data combined - Niels Arne Dam; Carlos Eduardo Carvalho; Jae Won Lee (Danmarks Nationalbank, 2015)
We use a standard sticky-price model to provide evidence on three mechanisms that can reconcile somewhat frequent price changes with large and persistent real effects of monetary shocks. To that end, we estimate a semi-structural model for the U.S. economy that allows for varying degrees of real rigidities, and cross-sectional heterogeneity in price stickiness. The model can extract some information about these two features of the economy from aggregate data, and discriminate between different distributions of price stickiness. Hence it can also speak to the debate about the role of sales and other temporary price changes in shaping the effects of monetary policy. Employing a Bayesian approach, we combine macroeconomic time-series data with information about empirical distributions of price stickiness derived from micro price data for the U.S. economy. Our estimates point to the presence of both large real rigidities and an important degree of heterogeneity in price stickiness. Moreover, cross-sectional distributions of price stickiness that factor out sales improve the empirical fit of the model. Our results suggest that bridging the gap between micro and macro evidence on nominal price rigidity may require the combination of several mechanisms.
Keywords: 330